Nosocomial infection caused by Methicillin- Resistant Staphylococcus aureus from different positions of Al-Fehaa Hospital-Basrah - et.al, Kuther H.Mehdi (Al-Qadisiyah Journal of Pure Science, 2017)
Ninety bacteria isolates were obtained from different areas in Al-Fehaa Hospital, this represents the operative theaters, wards and hallways of the hospital, the present studies showed that the prevalence of 27 Methecillin-resistant Staphylococcus aureus (MRSA) in nosocomial infections and their antibiotic resistant pattern to (Calvulanic acid, Amoxicillin, Clarithromycin, Vancomycin, Cefotaxin, Gentamycin)in concentrations (15, 20, 10, 30, 10, 30, 30)Î¼g/ml at respectivily. The isolates of MRSA were identified by biochemical tests and all isolates of MRSA were resistant to Vancomycin (30Î¼g/ml), Amoxicillin (30 Î¼g/ml), Gentamycin (10Î¼g/ml) and Clarithromycin(10Î¼g/ml)